2008
DOI: 10.3758/brm.40.4.940
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations in the study of delay discounting in intertemporal choice: A comparison of tasks and modes

Abstract: An experimental comparison of two commonly used delay-discounting procedures (binary choice and fill in the blank) and modes of administration (paper and pencil and computer based) was conducted. Statistically significant main effects were found for task type-steeper discounting was observed in the binary-choice taskbut not for mode of administration. As simple evidence of validity, hyperbolic curves consistently provided a better fit to the data than did exponential curves for both tasks. Further, magnitude e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
123
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 78 publications
9
123
1
Order By: Relevance
“…Some research has focused on comparing these separate methods of measuring delay discounting (e.g., Smith & Hantula, 2008). Other research has investigated the reliability of the measures themselves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some research has focused on comparing these separate methods of measuring delay discounting (e.g., Smith & Hantula, 2008). Other research has investigated the reliability of the measures themselves.…”
mentioning
confidence: 99%
“…The FITB method can also be completed quickly and theoretically identifies the exact indifference point because the participant produces an exact value. However, the FITB method may produce different indifference points than the traditional binary-choice method, possibly because it is more "cognitively demanding" (i.e., the participant has to decide how to interpret the question and then generate a value; Smith & Hantula, 2008).…”
mentioning
confidence: 99%
“…The data reflected in Figure 2 suggest that the present data resembled those typically reported. However, discounting for the monetary amount was not as steep as one might expect from the literature (e.g., Beck & Triplett, 2009;Smith & Hantula, 2008), especially given the delays used in the current study. This result may be related to the magnitude of our monetary amount (i.e., $100,000 vs. $10,000 in the Smith & Hantula, 2008, study).…”
Section: Discussionmentioning
confidence: 63%
“…Previous research has found that different methods of measuring delay discounting can result in different rates of discounting being observed (Smith & Hantula, 2008). Thus, if another method had been employed (e.g., the fillin-the-blank method; Chapman, 1996), different findings and conclusions might have resulted.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation